Association between intra-abdominal injured organs and abdominal compartment syndrome in patients with severe blunt trauma: A propensity score matched study using nationwide trauma registry in Japan - Komori, Akira; Iriyama, Hiroki; Kainoh, Takako; Aoki, Makoto; Abe, Toshikazu (PloS one, 2023)
Abdominal compartment syndrome (ACS) after blunt abdominal trauma is a rare complication that requires early recognition and subsequent surgical intervention for optimal outcome. We aimed to investigate how differences in injured abdominal organs affect ACS development in patients with severe blunt abdominal trauma. This nested case-control study used a nationwide registry of trauma patients, namely, the Japan Trauma Data Bank (JTDB), and only included patients aged ≥ 18 years with blunt severe abdominal trauma, defined as an AIS score of abdomen ≥ 3, sustained between 2004 and 2017. Patients without ACS were used as control subjects and identified using propensity score (PS) matching. Characteristics and outcomes between patients with and without ACS were compared and logistic regression was used to identify specific risk factors for ACS. Among 294,274 patients in the JTDB, 11,220 were eligible for inclusion before PS matching, and 150 (1.3%) developed ACS after trauma. PS matching led to the inclusion of 131 and 655 patients with and without ACS, respectively. Compared to controls, patients with ACS had higher number of injured organs in the abdomen and displayed a greater frequency of vascular and pancreatic injuries, need for blood transfusion, and disseminated intravascular coagulopathy, a complication of ACS. In-hospital mortality was higher in patients with ACS than those without ACS (51.1% vs. 26.0%, p < 0.01). Logistic regression analysis revealed that a higher number of injured organs in the abdomen [odds ratio (OR) (95% confidence interval [CI]): 1.76 (1.23-2.53)] and pancreatic injury [OR (95% CI): 1.53 (1.03-2.27)] were independently associated with ACS. Greater number of injured organs in abdomen and pancreatic injury are independent risk factors for the development of ACS.